Peace, jus gentium and ethics in the work of Pietro Tamburini (1737-1827) - Grazia Grasso (Cahiers d'Études du Religieux- Recherches Interdisciplinaires, 2023)
If the 18th century is characterized by the importance of the notion of tolerance, the law of peace is also a central concept there. Moreover, during the Enlightenment, the idea of the need to respect humanity in times of war emerged, which would later constitute the foundation of humanitarian law. In this context is also placed the literary production of Pietro Tamburini (1737-1827), a Jansenist abbot of Brescia and professor of law in Pavia. He was strongly influenced by the theories of natural law and by the authors of the École romande du droit naturel. However, the work of Tamburini constitutes a contribution hitherto ignored on the theme of peace.